Insights into the role of neutrophils in neuropsychiatric systemic lupus erythematosus: Current understanding and future directions - Sim, Tao Ming; Mak, Anselm; Tay, Sen Hee (Frontiers in Immunology, 2022)
Central nervous system (CNS) involvement of systemic lupus erythematosus (SLE), termed neuropsychiatric SLE (NPSLE), is a major and debilitating manifestation of the disease. While patients with SLE mostly complain of common neuropsychological symptoms such headache and mild mood disorders that may not even be technically attributed to SLE, many SLE patients present with life-threatening NPSLE syndromes such as cerebrovascular disease, seizures and psychosis that are equally challenging in terms of early diagnosis and therapy. While we are just beginning to unravel some mysteries behind the immunologic basis of NPSLE, advancements in the mechanistic understanding of the complex pathogenic processes of NPSLE have been emerging through recent murine and human studies. The pathogenic pathways implicated in NPSLE are multifarious and various immune effectors such as cell-mediated inflammation, autoantibodies and cytokines including type I interferons have been found to act in concert with the disruption of the blood-brain barrier (BBB) and other neurovascular interfaces. Beyond antimicrobial functions, neutrophils are emerging as decision-shapers during innate and adaptive immune responses. Activated neutrophils have been recognized to be involved in ischemic and infective processes in the CNS by releasing neutrophil extracellular traps (NETs), matrix metalloproteinase-9 and proinflammatory cytokines. In the context of NPSLE, these mechanisms contribute to BBB disruption, neuroinflammation and externalization of modified proteins on NETs that serve as autoantigens. Neutrophils that sediment within the peripheral blood mononuclear cell fraction after density centrifugation of blood are generally defined as low-density neutrophils (LDNs) or low-density granulocytes. LDNs are a proinflammatory subset of neutrophils that are increased with SLE disease activity and are primed to undergo NETosis and release cytokines such as interferon-α and tumor necrosis factor. This review discusses the immunopathogenesis of NPSLE with a focus on neutrophils as a core mediator of the disease and potential target for translational research in NPSLE.